2021
DOI: 10.1007/s10856-021-06490-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymeric fibrous microstructured biodegradable small-caliber tubular scaffold for cardiovascular tissue engineering

Abstract: Increasing morbidity of cardiovascular diseases in modern society has made it crucial to develop artificial small-caliber cardiovascular grafts for surgical intervention of diseased natural arteries, as alternatives to the gold standard autologous implants. Synthetic small-caliber grafts are still not in use due to increased risk of restenosis, lack of lumen re-endothelialization and mechanical mismatch, leading sometimes either to graft failure or to unsuccessful remodeling and pathology of the distal parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Moreover, an order of magnitude difference in elastic modulus was achieved, resulting in mechanical inhomogeneity. Finally, the polymeric scaffolds' toxicity evaluation revealed that the materials were safe and did not release any toxic and dangerous substances [ 96 ].…”
Section: Electrospun Nanofibrous Scaffolds For Tissue Engineering App...mentioning
confidence: 99%
“…Moreover, an order of magnitude difference in elastic modulus was achieved, resulting in mechanical inhomogeneity. Finally, the polymeric scaffolds' toxicity evaluation revealed that the materials were safe and did not release any toxic and dangerous substances [ 96 ].…”
Section: Electrospun Nanofibrous Scaffolds For Tissue Engineering App...mentioning
confidence: 99%
“…PCL tubular scaffolds have been developed that have the ability to mimic both the structure and the biomechanics of blood vessels. Dimopoulous et al fabricated biodegradable scaffolds which promoted cell infiltration and possessed excellent mechanical properties mirroring those of natural vessels [445]. PCL was also used in conjunction with fibrin to develop electrospun vascular grafts which also found to improve cell infiltration and proliferation [446].…”
Section: Electrospinningmentioning
confidence: 99%
“…On the other hand, PCL scaffolds for vascular tissue engineering were fabricated as support for the creation of a polymer-cell complex in vitro with subsequent implantation in vivo. Dimopoulos et al [ 95 ] verified the in vitro biocompatibility and cytotoxicity of electrospun PCL structures, as well as their significant effect on cellular behavior in vivo, i.e., their capability to induce cell attachment, migration, and differentiation. Additionally, the achieved fiber diameter, as well as mechanical properties of the produced scaffold, resulted comparable to the collagen fibers found in native vessels.…”
Section: Electrospinningmentioning
confidence: 99%